2021
DOI: 10.1039/d0nj05436d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and third order nonlinear optical properties of trans-A2B-type cobalt corroles

Abstract: Five trans-A2B-type cobalt corroles with different substituents at the 5,15 meso-phenyl positions exhibit an excellent third-order nonlinear optical performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…According to the literature reports, the peaks were ascribed to benzene stretching, CÀ C stretching together with the pyrrole bending and CÀ H bending, which came from the used corrole molecules. [36] The afore results revealed that corroles existed on the surface of the nanocomposites, which was consistent with the Raman result.…”
Section: Preparation and Characterization Of Nanocompositessupporting
confidence: 87%
See 2 more Smart Citations
“…According to the literature reports, the peaks were ascribed to benzene stretching, CÀ C stretching together with the pyrrole bending and CÀ H bending, which came from the used corrole molecules. [36] The afore results revealed that corroles existed on the surface of the nanocomposites, which was consistent with the Raman result.…”
Section: Preparation and Characterization Of Nanocompositessupporting
confidence: 87%
“…The Soret band is located at 412 nm for [Cu(OH‐Cor)] and 392 nm for [Co(OH‐Cor)(PPh 3 )], while the Q bands are located at 539 and 626 nm for [Cu(OH‐Cor)], 565 nm for [Co(OH‐Cor)(PPh 3 )] respectively. Anyway, both metal corroles [Cu(OH‐Cor)] and [Co(OH‐Cor)(PPh 3 )] showed the classical UV‐vis absorption spectra of copper and five‐coordinated cobalt corroles complexes in non‐binding solvent [36,37] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These combined systems have been reported to have a significant scope in optical devices. Later, the same group reported 51 the extensive synthesis of a series of trans -A 2 B-cobalt corroles, followed by a systematic investigation of the third-order NLO responses of the novel corroles via the Z -scan technique. In these NLO studies (open and closed aperture configurations), reverse saturation absorption and self-defocusing behavior were prominently revealed.…”
Section: Resultsmentioning
confidence: 99%
“…To revive the study of the potential of NLO in the field of telecommunication, photonics, biomedicine, and optical signal processing, several NLO moieties were designed through various π-conjugated organic molecules ( Mardar, 2006 ; Bures et al, 2012 ; Sofiani et al, 2016 ; Biswas et al, 2020 ). For this reason, a great variety of small organic molecules and macrocyclic systems, such as porphyrins ( Rao et al, 2000 ; Senge et al, 2007 ; Swain et al, 2014a ; Katturi et al, 2020b ; Rathi et al, 2020 ; Vijisha et al, 2020 ; Kumar et al, 2021a ), phthalocyanines ( de la Torre et al, 2004 ; Kumar et al, 2007 ; Swain et al, 2014b ; Zhang et al, 2014 ; Bharati et al, 2018 ; Venkatram et al, 2018a; Venkatram et al, 2018b; Bhattacharya et al, 2019a ; Bhattacharya et al, 2019b ; Bhattacharya et al, 2021 ), corroles ( Katturi et al, 2020a ; Lu et al, 2021 ), porphycenes ( Sarma et al, 2011 ; Swain et al, 2012 ; Pati et al, 2020 ), and BODIPY dyes ( Ngoy et al, 2019 ), have been investigated for their NLO properties. Of these systems, we are particularly interested in phthalocyanine-based macrocyclic systems toward these applications.…”
Section: Introductionmentioning
confidence: 99%